Análisis comparativo técnico – financiero entre sistemas constructivos para edificaciones con estructura de hormigón armado y estructura de acero mediante el desarrollo de una matriz de decisión - Iturralde Arias, Piter Andrés (2019)
The objective of this titration project is to carry out a comparative technical financial study between two of the building systems currently used in the construction sector in Ecuador. These systems mainly integrate reinforced concrete and structural steel as structural materials in order to establish a logical descriptive matrix that will allow us to make a decision after a cost analysis, control and planning of a building project. To carry out this study, we will analyze the interventions that each of the proposed structural systems has in the procreation of a real project, determining the advantages and limitations of a base project in both alternatives.